2013
DOI: 10.5539/ijb.v6n1p48
|View full text |Cite
|
Sign up to set email alerts
|

Impact of New Natural Biostimulants on Increasing Synthesis in Plant Cells of Small Regulatory si/miRNA With High Anti-Nematodic Activity

Abstract: Plant endoparasitic cyst nematode Heterodera schachtii Schmidt, gallic nematode Meloidogyne incognita and stem nematode Ditylenchus destructor damage various agricultural crops. The application of ecologically safe natural biostimulants with bioprotective properties is a newer approach for increasing plant resistance to parasitic nematodes. The molecular-genetic analysis of biostimulants action on plant genome is necessary for creation of new effective bioregulators for plant protection against phytopathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 47 publications
0
12
0
2
Order By: Relevance
“…Experimental evidence suggests that streptomycete-derived MBs stimulate growth and viability of crops, as has been recently demonstrated during in vitro, in vivo and greenhouse experiments on wheat [52,53,64], cucumbers [56], rapeseed [59], and Chinese cabbage [57]. Thus, we replace a constant growth rate of uninfected plants by a growing saturated function of the amount of applied MBs…”
Section: Model Derivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental evidence suggests that streptomycete-derived MBs stimulate growth and viability of crops, as has been recently demonstrated during in vitro, in vivo and greenhouse experiments on wheat [52,53,64], cucumbers [56], rapeseed [59], and Chinese cabbage [57]. Thus, we replace a constant growth rate of uninfected plants by a growing saturated function of the amount of applied MBs…”
Section: Model Derivationmentioning
confidence: 99%
“…with r (0) = r 0 and r (∞) = r 0 /s. Molecular genetic analyses show that MBs trigger a significant increase in the within-plant synthesis of si/miRNA homologous with plant genes associated with proteins that are important for a successful infection, as well as with viral genes, whose expression is needed for viral replication in plants [19,53,55,56,58,59]. To model this effect, we take the rate of disease transmission from infected vectors to plants in the form of a decreasing function of the amount of applied MBs as follows,…”
Section: Model Derivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Biostimulants developed on the basis of metabolites of these streptomycetes have also shown nematicidal effects on root-knot nematode M. incognita in vitro (Biliavska et al, 2015a), as well as bioprotective RNAi-mediated effects against cyst nematode H. schachtii in rape (Tsygankova et al, 2013, 2014a), Brassica rapa subs. pekinensis (Chinese cabbage) (Biliavska et al, 2016c), and sugar beet (Tsygankova et al, 2012b), as well as on both of these nematodes in sugar beet and cucumber (Tsygankova et al, 2014b). It should be noted that we are using the term “biostimulant” loosely to describe poly-component substances without discriminating them by the mode of their action, such as biopesticides, plant growth regulators etc., hence avoiding the need to abide by one of the more restrictive definitions Calvo et al, 2014; Brown and Saa, 2015; du Jardin, 2015; Nardi et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…At the Institute of Bioorganic Chemistry and Petrochemistry of NAS of Ukraine together with the National Enterprise Interdepartmental Science and Technology Center "Agrobiotech" of NAS and MES of Ukraine the several new ecologically safe plant growth regulators of synthetic origin: Ivin and natural origin: Emistim, Poteitin, Zeastimulin, Charkor, Biolan, Biogen, Radostim, Radostim-super, Regoplant and Stimpo that accelerate plant growth, increase yield crop of vegetables, grains, legumes and fruit crops, as well increase plant immune protection against pathogenic and parasitic organisms were created [27][28][29][30][31]. Our previous studies have shown the possibility of using of new synthetic and natural compounds in the isolated tissue cultures of agricultural and medicinal plants to induce morphogenetic processes and increase the synthesis of secondary metabolites [32][33][34].…”
Section: Introductionmentioning
confidence: 99%